AVALIAÇÃO DO SISTEMA DE TRATAMENTO DE RECLAMAÇÕES/DENÚNCIAS SOBRE PRODUTOS, PROCESSOS E SERVIÇOS AVALIADOS NO ÂMBITO DO SISTEMA BRASILEIRO DE AVALIAÇÃO DA CONFORMIDADE (SBAC) - Salles Filho, Mario (2004)
The purpose of this work is to analyze the demands of the society related to the process for treatment of complaints, denounces and appeals on products, processes and services with the assessment of conformity required, in the extent of the Brazilian Conformity Assessment System - SBAC, which Inmetro holds the control in Brazil. It also aims at a comparative study for that treatment, with the main entities of the countries that make use of the conformity assessment of their products and services, in order to attend the commercial demands of their internal markets and of the overall world, in way to make products, processes and services available to the consumers with quality and safety. In that way, it intends to identify the procedures, actions and the sources used in the processes of those entities, aiming at a possible comparative reference to improve our results and the consequent consumers satisfaction for those services. The comparison effect data used here came from the European Union. As a final result, it was proposed a few suggestions to improve the process for treatment of demands of the society by Inmetro.